2003
DOI: 10.1002/art.11072
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of deficient T cell receptor ζ chain restores T cell signaling and augments T cell receptor/CD3–induced interleukin‐2 production in patients with systemic lupus erythematosus

Abstract: Objective. T cells from a majority of patients with systemic lupus erythematosus (SLE) display antigen receptor-mediated signaling aberrations associated with defective T cell receptor (TCR) chain, a subunit of the TCR/CD3 complex. This study was undertaken to explore the possibility that forced expression of TCR chain may reverse the known signaling abnormalities and defective interleukin-2 (IL-2) production in SLE T cells.Methods. Freshly isolated SLE T cells were transfected with TCR chain construct in a eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 24 publications
(30 reference statements)
8
77
0
6
Order By: Relevance
“…This study further confirmed the need for FcR␥ expression to achieve robust DN T cell-mediated suppression. Reports have suggested that caspase-3 does not directly act on FcR␥ molecules, but rather functions by cleaving CD3 molecules, and the reduced levels of CD3 protein lead to increased FcR␥ expression (36,42). In other T cells, such as human effector CD4 ϩ T cells and tumor-infiltrating lymphocytes, up-regulation of FcR␥ is associated with down-regulation of CD3 expression (27,43).…”
Section: Discussionmentioning
confidence: 99%
“…This study further confirmed the need for FcR␥ expression to achieve robust DN T cell-mediated suppression. Reports have suggested that caspase-3 does not directly act on FcR␥ molecules, but rather functions by cleaving CD3 molecules, and the reduced levels of CD3 protein lead to increased FcR␥ expression (36,42). In other T cells, such as human effector CD4 ϩ T cells and tumor-infiltrating lymphocytes, up-regulation of FcR␥ is associated with down-regulation of CD3 expression (27,43).…”
Section: Discussionmentioning
confidence: 99%
“…The Amaxa Nucleofector technology is an electroporation-based method in which a combination of a specific nucleofector solution and specific electric parameters achieves delivery of plasmid DNA into the cell nucleus, thereby resulting in enhanced gene expression. This method is effective in transfecting hard-to-transfect cells such as T cells [26] and dendritic cells [27]. Using enhanced green fluorescent protein (eGFP) as the reporter, we demonstrate that nucleofection achieves greater than 60% transient transfection efficiency in mouse ES cells and increases stable transfection of mouse ES cells by 10-fold compared with electroporation.…”
Section: Introductionmentioning
confidence: 98%
“…There is also evidence that the deficiency of the TCR chain, which has been described in SLE patients, may be in part responsible for the supranormal Ca 2ϩ response mentioned above (39,61). This correlation has been reinforced by the recent report that transfectional correction of the TCR chain deficiency in lupus T cells leads to normalization of the cytoplasmic Ca 2ϩ fluxes (48).…”
Section: Sle (I) Cd40l Expression In Human Slementioning
confidence: 84%